Optimizing the Benefits of Mental Practice on Motor Acquisition and Consolidation with Moderate-Intensity Exercise - Rannaud Monany, Dylan; Lebon, Florent; Papaxanthis, Charalambos (Peer Community Journal)

(untitled)
The optimization of mental practice (MP) protocols matters for sport and motor rehabilitation. In this study, we were interested in the benefits of moderate-intensity exercise in MP, given its positive effects on the acquisition and consolidation of motor skills induced by physical practice (PP). Four experimental groups were tested: i) physical practice without exercise (PP-Rest), ii) mental practice without exercise (MP-Rest), iii) mental practice preceded by Exercise (Exe-MP), and iv) mental practice followed by Exercise (MP-Exe). We hypothesized that exercise before MP would further increase speed and accuracy at a finger-sequence task measured right after MP (potentiation of motor acquisition), whereas exercise after MP would further increase speed and accuracy the day after MP (promotion of motor consolidation). Motor performance (movement speed and accuracy) was measured during a sequential finger tapping task before (Pre-Test), immediately after (Post-Test 0h, acquisition), and one day after practice (Post-Test 24h, consolidation). Results suggest that exercise before MP did not additionally improve motor acquisition in comparison to the MP-Rest group (both for accuracy and speed, p’s>0.05). Interestingly, moderate-intensity exercise after MP further increased performance during motor consolidation (speed, p=0.051; accuracy, p=0.028), at the level of the PP-Rest group. This novel finding represents a promising advance in the optimization of mental practice protocols in sport-related and rehabilitation settings.